Perilaku Pemenuhan Gizi pada Ibu Menyusui di Beberapa Etnik di Indonesia - oktarina oktarina oktarina; Yurika Fauzia wardhani (Buletin Penelitian Sistem Kesehatan, 2019)
Balanced nutrition during breastfeeding is important for breastfeeding mothers because it affects breastmilk production. The fulfillment of good nutrition for breastfeeding mothers will affect the nutritional status and the growth of their babies. The concept of sick and healthy, food and drink that is good for health, trust and abstinence, on one hand, can be a barrier for health development but on the other one can be a potential for overcoming health problems. This study is a secondary data analysis, which is sourced from Health Ethnographic Research data in 2012, 2014 and 2015. Samples taken were from the Rote, Sabu and Madura ethnic groups. Data collected included breastfeeding mothers' behavior as well as the adequacy of nutrition for breastfeeding mothers in the three ethnic groups. The results showed that maternal behavior in newborns gave a prelactal type of food, where in the ethnic Rote in the form of coffee water or sugar water, in the ethnic Sabu in the form of a concoction of chili leaves that were pounded, filtered and taken the juice, and the Madura ethnic in the form of honey and young coconut water aimed to smoothen baby’s digestion. Abstrak Gizi seimbang penting bagi ibu menyusui karena sangat erat kaitannya dengan produksi air susu. Pemenuhan gizi yang baik akan berpengaruh terhadap status gizi ibu menyusui dan tumbuh kembang bayinya. Konsep tentang sehat-sakit, makanan-minuman yang baik untuk kesehatan, kepercayaan dan pantangan, di satu lain bisa menjadi penghalang namun di sisi lain bisa menjadi potensi untuk mengatasi permasalahan kesehatan. Penelitian ini merupakan analisis data sekunder, yang bersumber dari data Riset Etnografi Kesehatan tahun 2012, 2014 dan 2015 yang bertujuan untuk mengetahui perilaku pemenuhan gizi ibu menyusui pada etnik Sabu, Rote dan Madura. Data yang dikumpulkan meliputi perilaku ibu menyusui serta kecukupan zat gizi ibu menyusui pada tiga etnik tersebut. Hasil menunjukkan bahwa perilaku ibu pada bayi baru lahir memberikan jenis makanan prelaktal, dimana pada etnik Rote berupa air kopi atau air gula, pada etnik Sabu berupa ramuan daun cabai yang ditumbuk, disaring dan diambil sarinya, serta etnik Madura berupa madu dan air kelapa muda yang bertujuan untuk melicinkan pencernaan bayi.